iMeD: Self-monitoring mobile application for diabetic patient / Nurul Izzati Wahid - Wahid, Nurul Izzati (2020)
Diabetes is a common disease, and it can be classified as one of the non-communicable diseases (NCDs) in the world. It can be defined as a group of metabolic diseases that were identified by high blood sugar, which is results from a deficiency of insulin action, insulin secretion, or both. In pursuance of achieving and maintaining the blood sugar levels, diabetes self-care plays an important role. Those who are less adherent to diabetes self-care can exhibit a deterioration of glycemic levels. However, most of the patient has a poor understanding of the specific component of a well-balanced diet and the calories recommendation serving. Besides, they also faced difficulties to remember the timing to take their medication timing. Further to this, a self-monitoring mobile application named iMeD has been developed to overcome this problem. This application has implemented Data Visualization technique to enable the application to display information in a graphical format to give the user a better understanding of their calorie and carbohydrates intake per day. Besides, iMeD also able to recommend food based on their current restriction on daily calorie and carbohydrates intake by using Content-Based Filtering techniques. These can help the user who has a poor understanding of calorie recommendation serving. Also, iMeD will help to remind them about their medication and meal timing by using Push Notification.The significance of this project is it will develop an application that helps a diabetic patient by monitoring their diet and medication intake per day. The main reason this application being developed is to help the diabetic patient to prevent them from over intake carbohydrates in their daily meal because carbohydrates intake is correlated to blood sugar. In future, instead of focusing one operating system platform, iMeD may be supported by both platform, which are Android and iOS. Besides, the compatibility issue can be solved within the enhancement phase.